PENGGUNAAN ROLE PLAY PADA PENGUASAAN PASSIVE VOICE DI SALAH SATU SMA NEGERI DI SURABAYA - Yoga Kusumawardhana; Zainul Aminin (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Passive voice becomes highly crucial in preparing students to understand scientific texts and situations. Otherwise, students struggled with detecting and executing passive speech patterns. Students were obliged to use role play in mastering passive voice in order to promote their competency through implementation. Students' knowledge backgrounds were used to master passive voice through role play. Meanwhile, the researcher focused solely on typical passive voice patterns, such as simple present, present perfect, and simple past, according to scientific article in curriculum 2013. These tenses were also regularly presented in books/learning exercises that students and teachers have used in their classroom learning process. This study intended to find the significant difference in the use of role play in passive voice mastery to eleventh-grade students who have learned English in experience of arranging active voice sentences at Senior High School. This research utilized qualitative research with the design of quasi-experimental research to control and experiment groups. The researcher applied independent sample t-test to analyze data in overall effectiveness od the use of role play in passive voice mastery and paired test to find each group’s progress and find significant differences between pre-test and post-test in every group. As the result, this study provided no significant difference in passive voice mastery for students taught with role play and without role play. As suggestion, role play may not be a good approach to acknowledge students who consider English as foreign language to learn passive voice. However, it can be a good choice to resemble the conventional approach with role play to commense new learning environment.